2012
DOI: 10.1155/2012/570431
|View full text |Cite
|
Sign up to set email alerts
|

Training Self-Administered Acupressure Exercise among Postmenopausal Women with Osteoarthritic Knee Pain: A Feasibility Study and Lessons Learned

Abstract: Background. Osteoarthritis (OA) is more prevalent in women, particularly after menopausal age. Women are more likely to seek complementary and alternative medicine (CAM) approaches. We examined the feasibility of training self-administered acupressure exercise and assessed its impact on OA symptoms among women with knee OA. Methods. Thirty-six eligible postmenopausal women were randomly assigned in the acupressure exercise group (n = 15) or the control group (n = 21) for 12 weeks. Feasibility outcomes (e.g., c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 32 publications
1
47
1
Order By: Relevance
“…The low attrition rate, especially in comparison with Zhang and colleagues' study, 16 was likely attributed to two factors. One was that the RA in the current study could address participants' questions during weekly phone calls, an especially important factor in the early weeks of participation.…”
Section: Sample Retentionmentioning
confidence: 67%
See 2 more Smart Citations
“…The low attrition rate, especially in comparison with Zhang and colleagues' study, 16 was likely attributed to two factors. One was that the RA in the current study could address participants' questions during weekly phone calls, an especially important factor in the early weeks of participation.…”
Section: Sample Retentionmentioning
confidence: 67%
“…16,22 The hand-held device caused some discomfort and adverse events. Future studies should consider using other tools or just fingers to apply pressure.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…TCM theory holds that meridians, which are channels in a network of energy pathways throughout the body, regulate the flow of Qi (vital energy) and the unbalanced flow of Qi results in disease [16]. By applying pressure to acupoints (trigger or active points) on the surface of the skin, acupressure stimulates the meridians, resulting in the opening of the channels and balancing of energy, thus restoring health [14, 16]. Because acupressure uses the application of pressure to acupoints without penetrating the skin, it is non-invasive and painless [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…This technique has a number of advantages including flexibility, low cost, and empowerment [18]. Studies have reported on the clinical application of self-administered acupressure [14, 23]. In addition, systematic reviews of the effect of self-administered acupressure for symptom management have been conducted.…”
Section: Introductionmentioning
confidence: 99%